Application of Binocular Vision Algorithm Based on Measurement and Control Technology in Robot Measurement and Positioning (Informatica, 2024)
Due to the efficient application of computer vision technology in the field of automation industry, the research on robot measurement and positioning combined with binocular vision algorithms and visual guidance systems has become more advanced and complex. This paper studies the use of binocular vision information to construct spatial three-dimensional coordinates and then issue execution commands to the robot, so that the Geometric modeling of binocular stereo vision can meet the requirements of accurate measurement and positioning of the test target. The target matching algorithm for binocular stereo vision is analyzed and the most suitable block matching algorithm for machine perfusion is determined. It belongs to the local matching algorithm and has a calculation speed of 93 ms. Testing the left and right camera parameters and spatial coordinate positioning measurement results shows that the pixel focal lengths of the left camera are 8.10172 mm and 8.10407 mm; The pixel focal lengths of the right camera are 8.10140 mm and 8.10365 mm; The maximum projection error of the left and right cameras is 0.075 pixels. The maximum and average error results of the 29 honeycomb structural components tested afterwards were 1.16 mm, 0.63 mm, and 1.83 mm, 0.81 mm on the horizontal and vertical axes, respectively; The maximum error value in rotation angle is 3.56°, and the average value is 1.37°. The final result shows that the error remains roughly within 2 mm and 4°. The experimental data proves that the algorithm system has precise requirements for robot measurement and positioning, and provides a theoretical basis and technical reference for robot measurement and positioning.